(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wahyudi A, Sari MF, Rajamin I, Arsri M. 2023. Evaluation of proximate analysis and yield production of watermelon in Lampung, Indonesia. Biodiversitas 24: 6010-6015. The breeding of watermelon plants is carried out to produce new superior varieties. This study aimed to test the moisture, fat, carbohydrate, ash, and vitamin contents, and the yield potential of a hybrid watermelon line (F1). The materials used were 6 hybrid watermelon and 2 commercial lines as control varieties. A randomized block design was adopted in this study and was analyzed by LSD test, dendrogram, and proximate analysis. The result showed that the 6 hybrid watermelon lines had high yield potential. Furthermore, the moisture content of the fruit of the WM 2110-1204 lines (92.24%) was higher than other lines. Proximate data analysis showed that the WM 2110-0616 line had a higher ash content (0.16%), and the carbohydrate content of the fruit of the WM 2110-0806 line (3.64%) was also higher. The vitamin C-vitamin content of the fruit of the WM 2110-0308 line (0.36 mg.g-1) was higher, while the 4 watermelon lines, namely WM 2110-0308, WM 2110-204, WM 2110-0806, and WM 2110-1606 had advantages in terms of skin color and striation, fruit sweetness level and weight. In a dendrogram analysis, qualitative characters were divided into two clusters, with clusters I and II containing 8 and 1 lines, respectively.